A comparative study of mifepristone with dinoprostone for induction of labor in third trimester - Sivadas, Akshaya; Grover, Seema; Kaur, Harpreet; Goyal, Lajya Devi; Kaur, Khushpreet (International Journal of Research in Medical Sciences, 2024)
Background: Success of labor induction depends upon favourability of the cervix at the time of induction. Various methods have been tried for labor induction but the search for ideal induction agent continues. There is a paucity of literature regarding the safety and efficacy of Mifepristone as induction agent in live pregnancies. Our aim was to study the efficacy of tablet Mifepristone as a cervical ripening agent and to compare the feto-maternal outcome with Dinoprostone gel. Methods: A total of 100 patients who required labor induction were enrolled and randomized to receive mifepristone and dinoprostone. 50 patients were given oral tablet Mifepristone 200mg and 50 patients were instilled with intracervical Dinoprostone 0.5mg gel. The outcome was assessed by improvement in bishop’s score, induction delivery interval, requirement of oxytocin, mode of delivery, and feto-maternal complications. Results: The improvement in mean Bishop’s score after 24hours was more in Mifepristone group (2.78±1.28 to 7.22±2.02) than in Dinoprostone group (2.64±1.29 to 6.70±1.75) (p=0.173). The incidence of vaginal delivery and LSCS were 86% and 14% in Mifepristone group and 72% and 28% in Dinoprostone group, respectively (p=0.227). The requirement of mean dosage of oxytocin was lesser in Mifepristone group (2.26±0.71) as compared to Dinoprostone group (3.29±1.35) (p=0.001). NICU admission was required in 26% neonates in Dinoprostone group and 16% neonates in Mifepristone group (p=0.220). Conclusions: Mifepristone is a safe and efficient cervical ripening agent with no significant adverse effects to both mother and fetus.